QUANTITATIVE CHANGES OF MOTORIC ABILITIES CONDITIONED BY KINEZIOLOGY OPERATORS AT THE CHILDREN WITH SPECIAL NEEDS - Branimir Mikić; Izudin Tanović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
The basic mission of the physical training and health education of children with special needs is to satisfy bio-pshico-social need for motion as an expression of satisfying certain needs that can effect on adaptive and creative abilities in modern life circum stances, as well as, on development of health culture of pupils in order to preserve health, correction of inborn and acquired deviation during their growth in early childhood. The most important goal of this research was to define transformation process of basic-motoric abilities, under the influence of experimental program with special needs pupils categorized in light and moderate category of retardation. The research was performed with the children in the "Centre for special needs children youth".Sample was made with girls and boys, with total of 71 children devided in to three sub-sample according to gender, age and level of retardation. Euro-fit battery was taken as an instrument of research.During this research it was concluded that systematic influence of kineziology operators can positively influence on improved motoric functions of special needs children which is directly refered to intelectual abilities(balance and orientation).